Templated formation of porous Mn2O3 octahedra from Mn-MIL-100 for lithium-ion battery anode materials. (15th May 2016) - Zhang, Bowei; Hao, Shiji; Xiao, Dongrong; Wu, Junsheng; Huang, Yizhong
Abstract: Octahedral Mn-MIL-100 metal-organic frameworks (MOFs) are first synthesized, which are then used as templates to fabricate the porous Mn2 O3 octahedra through a post-calcination strategy. The morphologies and crystalline structures of as-prepared Mn2 O3 octahedra are performed by using field-emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and transmission electron microscopy (TEM). A reversible lithium storage capacity as high as 755 mA h/g at 0.2 C after 100 cycles is measured from Lithium-ion batteries (LIBs) where the porous Mn2 O3 octahedra are acted as anode. Such a high performance indicates that the porous Mn2 O3 structure is an excellent anode candidate of LIBs with high capacity and long-life cycling stability. Graphical abstract: Highlights: Porous Mn2 O3 octahedra have been fabricated from Mn-MIL-100 MOFs templates. SEM, XRD and TEM were used to characterize the morphologies and crystalline properties. As-prepared Mn2 O3 octahedra were evaluated as an anode material in LIBs. High lithium storage capability and outstanding cycling stability were demonstrated.